Problemas de aç\~ao coletiva: Cooperaç\~ao e deserç\~ao - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Many public policies seek to promote, maintain, modify or improve collective actions. The development of a country requires actions that are complex and wide in scope. This and following texts sort out: i) two general classes of problem-situations that lack collective action; and ii) kinds of mechanisms that are useful as possible solutions to such problem-situations; i.e., mechanisms for acting upon institutions (organizations; formal or legal norms; formal practices) or upon cultural elements (social customs; customary morality; customary values and beliefs) of a society. In these texts, a leitmotif is the strategic dimension, one of the dimensions of building or changing institutions and cultural elements. To this end, one takes advantage of basic games of strategy as simple models for assigning those problems into classes. This first text deals with the problem-situation of cooperation vs. defection, modeled as prisoner's dilemma games. It covers situations of disputes for exits during disasters; of party leaders that become candidates for losing elections; of groupthink in committees; of lack of interest in training employees; of bottlenecks in urban traffic; of creating new city or state governments; of bank runs to financial safety; of tragedies of commons, be they environmental or otherwise.
Keywords: H41; Z13; Z18; 330; collective action; institutional change; prisoner's dilemma